Exploring a facile preparation method for Co-Ni/MoS2-derived nanohybrid from wheat straw extract and its physicochemical properties - Himanshu M.; Singh A.; Verma B.; Pandey S.K.; Syed A.; Elgorban A.M.; Wong L.S.; Mohammad A.; Srivastava N. (My University, 2025)
This study presents a novel approach for the fabrication of a Co,Ni/MoS2-derived nanohybrid material using wheat straw extract. The facile synthesis method involves a sol–gel process, followed by calcination, showcasing the potential of agricultural waste as a sustainable reducing and chelating reagent. The as-prepared nanohybrid has been characterized using different techniques to analyse its physicochemical properties. X-ray diffraction analysis confirmed the successful synthesis of the nanohybrid material, identifying the presence of NiMoO4, CoSO4 and Mo17O47 as its components. Fourier-transform infrared spectroscopy differentiated the functional groups present in the wheat straw biomass and those in the nanohybrid material, highlighting the formation of metal–oxide and sulphide bonds. Scanning electron microscopy revealed a heterogeneous morphology with agglomerated structures and a grain size of around 70 nm in the nanohybrid. Energy-dispersive X-ray spectroscopy analysis shows the composition of elements with weight percentages of (Mo) 9.17%, (S) 6.21%, (Co) 12.48%, (Ni) 12.18% and (O) 50.46% contributing to its composition. Electrochemical analysis performed through cyclic voltammetry showcased the exceptional performance of the nanohybrid material as compared with MoS2, suggesting its possible applications for designing biosensors and related technologies. Thus, the research study presented herein underscores the efficient utilization of natural resources for the development of functional nanomaterials with promising applications in various fields. This study paves a way for manufacturing innovation along with advancement of novel synthesis method for sustainable nanomaterial for future technological developments. © 2024 John Wiley & Sons Ltd.